2021
DOI: 10.34306/att.v3i2.211
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Islamic Religious Learning Innovation Technology with the iLearning Approach

Abstract: The field of education has an important role for a country in producing high-quality young generations so that they can be responsible for advancing the country. This important role is in line with the function of education, which is to develop abilities and shape the character and civilization of a dignified nation in order to educate the nation's life. Seeing the importance of education for the nation's next generation, it is necessary to innovate quality learning methods from childhood education to educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Similarly, this statement was mentioned by [26] in her study that the mobile application must be able to allow users to adjust image size based on their preferences. Meanwhile, [13] stated that the use of photographs for concrete places and people while icons, pictograms and symbols for abstract terms is appropriate. Sharing the same opinion is [8] who said that the picture can be drawings, photographs and symbolic images.…”
Section: A Multimedia Elements (Apps For Autism)mentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, this statement was mentioned by [26] in her study that the mobile application must be able to allow users to adjust image size based on their preferences. Meanwhile, [13] stated that the use of photographs for concrete places and people while icons, pictograms and symbols for abstract terms is appropriate. Sharing the same opinion is [8] who said that the picture can be drawings, photographs and symbolic images.…”
Section: A Multimedia Elements (Apps For Autism)mentioning
confidence: 99%
“…For example, use a picture of real food instead of illustrated food. The research in [13] similarly reported that an application should use real images to represent people and places.…”
Section: A Multimedia Elements (Apps For Autism)mentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmaceutical salt is a widely used raw material used, among others, as an ingredient raw materials for infusion preparations, tablet production, vaccine solvents, syrups, ORS, blood washing fluids, health drinks and others. In the cosmetic field, pharmaceutical sodium chloride is used as an ingredient in soap, ORS, shampoo, infusion, and dialysate fluids [21].…”
mentioning
confidence: 99%